Identification Important Factors of Cloud Computing On Business Growth with Consideration of Consumers Preference - Himani R. Gandhi; Dr. Bhawesh Kumawat (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
Analysing key factors influencing their preferences. The findings reveal that cost efficiency is the most crucial factor, emphasizing the demand for affordable cloud solutions. Data privacy ranks second, reflecting concerns about cybersecurity and regulatory compliance. Scalability and flexibility are the least prioritized factor, indicating that businesses may not require highly scalable infrastructure immediately. Among cloud computing tools, Google Drive is the most preferred platform, highlighting a strong inclination toward cost-effective and user-friendly storage solutions. Dropbox follows as another popular choice. Among enterprise-level services, Amazon Web Services (AWS) leads, followed by Google Cloud Platform and Microsoft Azure, showcasing increasing adoption of robust cloud infrastructure solutions. IBM Cloud and Oracle Cloud exhibit lower adoption, suggesting niche applications. Chi-square analysis revealed significant associations between most cloud computing tools and key factors like scalability, cost efficiency, and data privacy, except for Oracle Cloud and IBM Cloud in some cases. These insights could guide cloud service providers in enhancing their offerings by focusing on affordability, security, and scalability to better meet the needs of businesses and consumers in Surat City.